Janus Composite Nanotubes. Issue 12 (24th May 2016) - Chen, Ying; Liu, Zhen; Qu, Xiaozhong; Liang, Fuxin; Yang, Zhenzhong
Abstract: We propose a facile method to achieve paramagnetic Janus nanotubes with two compositions compartmentalized onto the interior and exterior surfaces, respectively. A sulfonated polydivinylbenzene (PDVB) nanotube is prepared by simple sulfonation of the exterior surface of a PDVB nanotube. Silica@FeOOH dual layers are sequentially grown onto the sulfonated PDVB nanotube surface. The composite nanotubes become paramagnetic after calcination and can be broken into shorter pieces under vigorous ultrasonication. After selective modification of the interior and exterior surfaces of the paramagnetic nanotubes, the nanotube shell becomes Janus in wettability. Desired hydrophobic species can be selectively captured inside the cavity. The paramagnetic Janus composite nanotubes can align into parallel chains under a magnetic field, which is self‐disassembled upon removal of the magnetic field. Abstract : Inside and out : A facile method yields a novel superparamagnetic Janus nanotube with anisotropic morphology. FeOOH is introduced onto the sulfonated polydivinylbenzene (PDVB) tubes and subsequently coated with a thin layer of silica. The composite nanotubes become superparamagnetic after calcination. Selective modification of the interior and exterior surfaces yields superparamagnetic nanotubes with Janus shells. Desired species can be selectively captured into the cavity of the Janus nanotubes from their surroundings.